Functions of FKBP12 and Mitochondrial Cyclophilin Active Site Residues In Vitro and In Vivo in Saccharomyces cerevisiae - Dolinski, Kara (The American Society for Cell Biology, 1997)
Cyclophilin and FK506 binding protein (FKBP) accelerate cis–trans peptidyl-prolyl isomerization and bind to and mediate the effects of the immunosuppressants cyclosporin A and FK506. The normal cellular functions of these proteins, however, are unknown. We altered the active sites of FKBP12 and mitochondrial cyclophilin from the yeast Saccharomyces cerevisiae by introducing mutations previously reported to inactivate these enzymes. Surprisingly, most of these mutant enzymes were biologically active in vivo. In accord with previous reports, all of the mutant enzymes had little or no detectable prolyl isomerase activity in the standard peptide substrate-chymotrypsin coupled in vitro assay. However, in a variation of this assay in which the protease is omitted, the mutant enzymes exhibited substantial levels of prolyl isomerase activity (5–20% of wild-type), revealing that these mutations confer sensitivity to protease digestion and that the classic in vitro assay for prolyl isomerase activity may be misleading. In addition, the mutant enzymes exhibited near wild-type activity with two protein substrates, dihydrofolate reductase and ribonuclease T1, whose folding is accelerated by prolyl isomerases. Thus, a number of cyclophilin and FKBP12 “active-site” mutants previously identified are largely active but protease sensitive, in accord with our findings that these mutants display wild-type functions in vivo. One mitochondrial cyclophilin mutant (R73A), and also the wild-type human FKBP12 enzyme, catalyze protein folding in vitro but lack biological activity in vivo in yeast. Our findings provide evidence that both prolyl isomerase activity and other structural features are linked to FKBP and cyclophilin in vivo functions and suggest caution in the use of these active-site mutations to study FKBP and cyclophilin functions.